2013
DOI: 10.5194/bg-10-315-2013
|View full text |Cite
|
Sign up to set email alerts
|

Effect of increased <i>p</i>CO<sub>2</sub> on the planktonic metabolic balance during a mesocosm experiment in an Arctic fjord

Abstract: Abstract. The effect of ocean acidification on the balance between gross community production (GCP) and community respiration (CR) (i.e., net community production, NCP) of plankton communities was investigated in summer 2010 in Kongsfjorden, west of Svalbard. Surface water, which was characterized by low concentrations of dissolved inorganic nutrients and chlorophyll a (a proxy of phytoplankton biomass), was enclosed in nine mesocosms and subjected to eight pCO 2 levels (two replicated controls and seven enhan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 44 publications
(58 reference statements)
2
43
1
Order By: Relevance
“…Primary production estimates obtained with the 14 Cmethod at 1 m depth exceeded O 2 gross community production (GCP) determined at 4 m depth by a factor of ∼ 2 (Tanaka et al, 2013), and O 2 -and DIC-based net community production (NCP) by a factor of 3-4 . These discrepancies were mainly due to the different amount of light that cells received during the various measurements, and are comparable to differences observed for polar phytoplankton along comparable depth and light gradients (Yun et al, 2012).…”
Section: C Primary Productionmentioning
confidence: 87%
See 3 more Smart Citations
“…Primary production estimates obtained with the 14 Cmethod at 1 m depth exceeded O 2 gross community production (GCP) determined at 4 m depth by a factor of ∼ 2 (Tanaka et al, 2013), and O 2 -and DIC-based net community production (NCP) by a factor of 3-4 . These discrepancies were mainly due to the different amount of light that cells received during the various measurements, and are comparable to differences observed for polar phytoplankton along comparable depth and light gradients (Yun et al, 2012).…”
Section: C Primary Productionmentioning
confidence: 87%
“…mesocosms was highest at low CO 2 concentration during the later phase of the experiment, i.e., after day 21 (Tanaka et al, 2013;Silyakova et al, 2012). A different or even anti-correlated response of PP and NCP to increasing pCO 2 would have important implications for carbon and oxygen cycling in the surface ocean.…”
Section: Primary Production Vs Net Community Productionmentioning
confidence: 98%
See 2 more Smart Citations
“…Tolerance of CO 2 levels up to ∼ 1000 µatm has often been observed in natural phytoplankton communities in regions exposed to fluctuating CO 2 levels. In these communities, increasing CO 2 often had no effect on primary productivity (Tortell et al, 2000;Tortell and Morel, 2002;Tortell et al, 2008b;Hopkinson et al, 2010;Tanaka et al, 2013;Sommer et al, 2015;Young et al, 2015;Spilling et al, 2016) or growth (Tortell et al, 2008b;Schulz et al, 2013), although an increase in primary production has been observed in some instances (Riebesell, 2004;Tortell et al, 2008b;Egge et al, 2009;Tortell et al, 2010;Hoppe et al, 2013;Holding et al, 2015). These differing responses may be due to differences in community composition, nutrient supply, or ecological adaptations of the phytoplankton community in the region studied.…”
Section: Ocean Acidification Effects On Phytoplankton Productivitymentioning
confidence: 89%